School Head Supervision as a Catalyst for Science Teacher Professional Growth - Km Indu,; Neetu M Shukla,; Nandita Deb, (The Bioscan, 2025)
This study examines how school heads’ supervisory practices can support science teacher learning. The research was designed using a mixed-methods approach, gathering quantitative data from teachers through questionnaires and qualitative data from school leaders in the form of interviews and FGDs with educators. Quantitative data show a highly positive attitude toward supervision in which high scores of agreement (the rates of consistent questions admitting should be observed higher than 82%.) with strong influences on methods of teaching, understanding the content and leadership. These results were verified in the qualitative analysis that uncovered themes. According to school leaders, their role is to support and assist as mentor and resources. Educators explained how positive, dialogic feedback resulted in them feeling more empowered and trusted to undertake reflective practice and they developed from ineffective teaching methods to better practices which encompassed hands-on science activities. The equipoise evidence map suggests that site-based supervision works better as a developmental, collegial process than a chastising test. Results The results of the apprenticeship supervision practices programme study show that creating a training network in developmental supervision is essential to help instill in teachers a culture of ongoing professional development and also for improving science education.